Analysis Of The Impact Of Social Investment Using The Sroi Method In The Mina Padi Program In Sungai Rebo Village, Banyuasin District - Dina, Rahma; Arbi, Muhammad (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2023)
The aims of this study were (1) to describe what the Mina Padi program was carried out by PT Pertamian RU III Plaju in the Sungai Rebo area for the community in Sungai Rebo village, (2) to calculate the monetization value from SROI calculations for the Mina Padi program in the village Sungai Rebo, (3) Analyzing the value of the reciprocal ratio of social investment in the implementation of PT Pertamian RU III Plaju's CSR program in Sungai Rebo Village, Banyuasin Regency. In this study, the SROI forecasting method was used to process Mina Padi program data where SROI is an analytical tool that measures the impact or benefits of a program, where later the outcomes of all activities carried out during this program are monetized into currency values, SROI forecasting itself is a method which is used for forecasting the value of the outcome of the Mina Padi program for the next 4 years. The Mina Padi Program is a program of CSR Pertamina RU III where the activities are carried out in Sungai Rebo Village, Banyuaasin I District, Banyuasin Regency, this Mina Padi program is not only in the form of rice but also integrated agriculture (rice, fish, ducks and vegetables), the purpose of this program is itself is to increase knowledge, skills, raise the standard of living of farmers, as well as to empower the people in the Rebo River. The SROI ratio of the Mina Padi program is as follows: (1) In calculating the SROI ratio every year, a positive value is obtained where the value of the SROI ratio is more than 1, which means that every IDR 1 invested will get a value that is more than the initial cost. invested, (2) In 2022 the SROI ratio value is 3.529, in 2023 the SROI ratio value is 3.028, in 2024 the SROI ratio value is 2.619 and in 2025 the SROI ratio value is 1.404, where the SROI ratio value is from 2022 – 2025 is worth > 1, which means that the Mina Padi program is able to produce a positive impact that exceeds the initial investment provided.